EDUCATION VALUE ISLAMIC CHARACTER IN THE FIVE TOWERS COUNTRY FILM - Abdillah Abdillah; Ridwan Ridwan (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2020)
This research is a descriptive study with a qualitative approach to Content Analysis techniques ( qualitative content analysis ). Subject of research is a film of State Lima Tower bouquet Ahmad ceremony. This study aims to reveal the value of Islamic character contained in the Five Towers Film . From the results of research that there are many educational values in the film, namely: Having a spirit of change, Integrity, Unyielding, Tolerance, Great Soul, Cooperation, creative and Independent.